Analisis Perbandingan Rasio Keuangan Untuk Menilai Kinerja Keuangan Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2020 – 2024 - Lestari, Dwi Tri Okta Meliana; Sasanti, Elin Erlina; Isnaini, Zuhrotul (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to analyze and compare the financial performance of food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research uses a descriptive quantitative approach with secondary data obtained from the companies’ annual financial reports. The population in this study includes all food and beverage sub-sector companies, while the sample was selected using purposive sampling based on specific criteria, namely companies that consistently published financial reports over five years and did not experience consecutive losses. The data analysis method used is financial ratio analysis, consisting of liquidity, solvability, activity, and profitability ratios. The analysis was conducted using a time series approach to observe changes over time, and a cross-sectional approach to compare performance among companies in the same period. The results of the study indicate that, in general, the financial performance of the companies is in relatively good condition, as reflected in stable liquidity and profitability ratios. However, some companies recorded extremely high or negative ratios, particularly in profitability, which may require further review of the data or financial conditions of the companies involved.